STRATEGI SELF-CARE DALAM PENANGANAN STRES PASCA PENSIUN MELALUI TEORI COPING LAZARUS PADA FILM THE INTERN - Wafiq Luthfiya Tahta Salsabila; Erindah Dimisyqiyani; Amaliyah; Gagas Gayuh Aji; Rizky Amalia Sinulingga (PT. Hasba Edukasi Mandiri, 2025)
Retirement is a significant life transition often accompanied by psychological stress due to the loss of role, routine, and identity. However, many retirees lack effective strategies to manage this stress, leading to decreased well-being. This study aims to interpret the self-care strategies employed by the character Ben Whittaker in the film The Intern (2015) to cope with post-retirement stress, analyzed through the lens of Lazarus & Folkman's coping theory. Using a qualitative descriptive case study design, the data from the film were analyzed through thematic analysis based on Lazarus & Folkman's coding framework (primary appraisal, secondary appraisal, problem-focused coping, emotion-focused coping). The results show that Ben's self-care process begins with an honest primary appraisal of his losses as a threat, triggering reflective emotion-focused coping. He then proactively engages in problem-focused coping by creating new routines and seeking challenging roles, while simultaneously maintaining emotional balance through social connectivity and positive nostalgia. The pinnacle of his adaptation is the mature integration of both coping strategies to navigate complex interpersonal dilemmas. Theoretically, this study enriches the transactional model by illustrating the dynamic, non-linear integration of coping strategies in later life. Practically, it offers a narrative model for developing psychosocial interventions that emphasize agency, social reconnection, and holistic self-care for retirees, suggesting that educational modules based on this film could facilitate healthy coping discussions.